Analisis Laporan Keuangan Untuk Meningkatkan Kinerja Keuangan Pada Koperasi BMT NUKAS Kabupaten Bojonegoro - Aulia Zahrotun Nafisah; Iwan Asmadi; Tri Lestari (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the Financial Performance of the BMT NUKAS Cooperative in Bojonegoro Regency during the 2020-2022 period. This research will assist in making decisions and determining policies in the future, especially in terms of the financial performance of cooperatives. The variable in this study is financial performance, with a population and sample of all financial report data, especially balance sheets and income statements for the period 2020 - 2022. Meanwhile, the data analysis technique used is ratio analysis with criteria based on the Decree of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 06/Per/M.KUKM/V/2006. The results showed that the financial performance of the BMT NUKAS Cooperative in Bojonegoro Regency (1) based on the liquidity ratio: a) Current Ratio average value of 92.72% in very unhealthy conditions. b.) Quick Ratio average value of 96.46% in very unhealthy conditions. c) Cash Ratio average value of 9.60% in very unhealthy conditions (2) solvency ratio: a) Total Assets to Debt Ratio has an average of 106.56% including in unhealthy conditions. b) Total Equity to Debt Ratio has an average of 6.56% in unhealthy conditions (3) profitability ratios: a) Return On Investment has an average of 58.01% in healthy conditions b) Return On Equity has an average an average of 13.61% in unhealthy conditions.